2019
DOI: 10.1002/adma.201904411
|View full text |Cite
|
Sign up to set email alerts
|

Stable and High‐Power Calcium‐Ion Batteries Enabled by Calcium Intercalation into Graphite

Abstract: Calcium‐ion batteries (CIBs) are considered to be promising next‐generation energy storage systems because of the natural abundance of calcium and the multivalent calcium ions with low redox potential close to that of lithium. However, the practical realization of high‐energy and high‐power CIBs is elusive owing to the lack of suitable electrodes and the sluggish diffusion of calcium ions in most intercalation hosts. Herein, it is demonstrated that calcium‐ion intercalation can be remarkably fast and reversibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
102
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 107 publications
(102 citation statements)
references
References 40 publications
0
102
0
Order By: Relevance
“…A more recent study also revealed that the room-temperature electrochemical insertion of Ca 2+ in a graphite electrode is feasible utilizing the co-intercalation reaction (Park et al, 2019). Park et al demonstrated that a graphite cell with 0.5 M Ca(BH 4 ) 2 in dimethylacetamide (DMAc) as the electrolyte exhibited a reversible capacity of 97 mAh g −1 at the first cycle, which was stably retained in subsequent cycles.…”
Section: Multi-valent Cation Co-intercalationmentioning
confidence: 99%
See 4 more Smart Citations
“…A more recent study also revealed that the room-temperature electrochemical insertion of Ca 2+ in a graphite electrode is feasible utilizing the co-intercalation reaction (Park et al, 2019). Park et al demonstrated that a graphite cell with 0.5 M Ca(BH 4 ) 2 in dimethylacetamide (DMAc) as the electrolyte exhibited a reversible capacity of 97 mAh g −1 at the first cycle, which was stably retained in subsequent cycles.…”
Section: Multi-valent Cation Co-intercalationmentioning
confidence: 99%
“…In operando XRD data suggested that an analogous staging process to that of Na co-intercalation occurred in the Ca electrochemical cell, confirming the co-intercalation. Additionally, a possible Ca 2+ -DMAc complex structure was proposed based on the results of solid-state nuclear magnetic resonance (NMR) and DFT calculation, as depicted in Figure 6E (Park et al, 2019). Prabakar et al reported that the use of 1 M Ca(TFSI) 2 in tetraglyme as the electrolyte could also enable Ca 2+ -ion intercalation together with the ether solvent.…”
Section: Multi-valent Cation Co-intercalationmentioning
confidence: 99%
See 3 more Smart Citations